Repeated Lobbying by Commercial Lobbyists and Special Interests - Thomas Groll; Christopher J. Ellis (Center for Economic Studies and ifo Institute (CESifo), 2016)
Using a model of repeated agency, we explain previously unexplained features of the real-world lobbying industry. Lobbying is divided between direct representation by special interests to policymakers, and indirect representation where special interests employ professional intermediaries called commercial lobbyists to lobby policymakers on their behalf. Our analytical structure allows us to explain several trends in lobbying. For example, using the observation that in the U.S. over the last 20 years policymakers have spent an increasing amount of their time fundraising as opposed to legislating, we are able to explain why the share of commercial lobbyist activity in total lobbying has risen dramatically and now constitutes over 60% of the total. The key scarce resource in our analysis is policymakers' time. They allocate this resource via implicit repeated agency contracts which are used to incent special interests and commercial lobbyists to provide a mix of financial contributions and information on policy proposals. These implicit agency contracts solve both an information problem in the presence of unverifiable policy information and a contracting problem in the absence of legal enforcement. These repeated relationship, that are often described using the pejorative term cronyism in the popular press, may in certain circumstances be welfare improving.
Keywords: D72; D78; D83; H11; P16; 330; lobbying; political access; intermediaries; information acquisition; financial contributions